The Drazin inverses of infinite triangular matrices and their linear preservers - Słowik, R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We consider the ring of all infinite $(N × N)$ upper triangular matrices over a field $F$. We give a description of elementsthat are Drazin invertible in this ring. In the case where $F$ is such that $char(F) ot = 2$ and $| F| > 4$, we find the form oflinear preservers for the Drazin inverses.